Polyimide aerogel/aramid fiber composite with high mechanical strength and thermal insulation for thermal protective clothing - Liu, Yuhang; Wang, Donglin; Li, Jie (Frontiers in Materials, 2023)
Polyimide (PI) aerogel, as a new organic aerogel material, has the excellent thermal properties of polyimide and the characteristics of high thermal insulation of aerogel, and has been paid increasingly attention. In the work, PI aerogel was used as the matrix material, and aramid fiber was used as reinforcement material, controllable flexible PI aerogel/aramid fiber composite insulation materials were successfully prepared by freeze-drying and soft treatment. This study sought to determine how the mass percentage of PI aerogel affected the microstructure, mechanical characteristics, thermal insulation capabilities, and thermal comfort of clothes in PI aerogel/aramid fiber composites. To achieve this, the preparation process of PI aerogel was optimized and the effects of different mass fractions of PI aerogel on the properties of the composite material were evaluated. The results demonstrated that increasing the mass fraction of PI aerogel led to improvements in the mechanical properties, flexibility, and heat insulation properties of the composite material. Furthermore, the PI aerogel/aramid fiber composite offered enhanced thermal comfort to the wearer in hot and humid environments, indicating that the composite material is particularly suited for thermal insulation applications.